Modeling Of A New Torque Controller For Direct Torque Control Of Induction Machines - Idris, Nik Rumzi; Yatim, Abdul Halim (2000)
In this paper a new torque controller for direct torque control (DTC) of induction motor drives is proposed. The structure of the new controller is very simple with its output similar to that of the conventional three level hysteresis comparator. The approximate frequency domain model of the proposed controller is presented which served as a guide for the selection of the controller's parameters. The simulation of the DTC of IM with the proposed torque controller is presented which is verified by experimental results. The results indicate that the proposed controller is capable of maintaining the torque switching frequency constant and reducing the torque ripple, particularly at low speed